Inclusion of Pregnant Girls and Teenage Mothers in Ugandan Schools: A Proposed Phenomenological Research. - Bukenya, Aloysius Lwanga; Ayikoru, Joyce (Student's Journal of Health Research Africa, 2022)
Background Research is proposed to explore a new feature in Uganda’s secondary schools because they have been advised and given guidelines to admit pregnant girls and teen mothers, a practice that is unprecedented in the country’s educational history. Many schools have responded to give this cluster of girls an opportunity to continue with mandatory education. The advice and guidelines are founded on large numbers of girls who during the Covid-19 lockdowns became teen mothers. Available literature indicates that at least 644,955 teen pregnancies were reported during the Covid-19 lockdowns of 2020 and 2021. The ministerial advice for schools to admit pregnant girls and teen mothers has come with mixed reactions, particularly from religious leaders. It is due to those mixed reactions that a study is proposed to examine issues that have arisen as a result of those unprecedented developments. Methodology: The research is adopting phenomenology as an educational qualitative research design whose aim is to explore the experiences of the research population and their consciousness of the phenomenon. The phenomenon is motherhood, for an adolescent schoolgirl, and the issues around it. The study’s research population is school teen mothers and pregnant girls. Discussion: To guide this study is the theory of metaphysical ethics which posits that moral order is rooted in the metaphysics of a human person. In this study, the right to education is conceptualized as the moral good that emanates from philosophical anthropology, and the dignity of a pregnant girl or a teen mother is proposed as the metaphysical justification for their admission to school to acquire what is their due. Strategies for pastoral care in education will be analyzed.